2020
DOI: 10.1038/s42003-020-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Anion-exchange chromatography mass spectrometry provides extensive coverage of primary metabolic pathways revealing altered metabolism in IDH1 mutant cells

Abstract: Altered central carbon metabolism is a hallmark of many diseases including diabetes, obesity, heart disease and cancer. Identifying metabolic changes will open opportunities for better understanding aetiological processes and identifying new diagnostic, prognostic, and therapeutic targets. Comprehensive and robust analysis of primary metabolic pathways in cells, tissues and bio-fluids, remains technically challenging. We report on the development and validation of a highly reproducible and robust untargeted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 33 publications
0
72
0
5
Order By: Relevance
“…Central carbon metabolism includes the carbon utilization pathways of glycolysis, the citrate cycle, and the pentose phosphate pathway. Many diseases have changes in central carbon metabolism, including cancer, diabetes, and heart disease (Walsby-Tickle et al, 2020 ). Schraw et al ( 2019 ) showed that changes in central carbon metabolism and amino acid metabolism were related to minimal residual disease (MRD) positivity and that metabonomics has potential utility in the risk prediction and targeted treatment of pediatric acute lymphoblastic leukemia (ALL).…”
Section: Discussionmentioning
confidence: 99%
“…Central carbon metabolism includes the carbon utilization pathways of glycolysis, the citrate cycle, and the pentose phosphate pathway. Many diseases have changes in central carbon metabolism, including cancer, diabetes, and heart disease (Walsby-Tickle et al, 2020 ). Schraw et al ( 2019 ) showed that changes in central carbon metabolism and amino acid metabolism were related to minimal residual disease (MRD) positivity and that metabonomics has potential utility in the risk prediction and targeted treatment of pediatric acute lymphoblastic leukemia (ALL).…”
Section: Discussionmentioning
confidence: 99%
“…Terminal fed blood samples were assessed for low‐molecular‐weight metabolites with liquid chromatography‐mass spectrometry (LC‐MS) within the Department of Chemistry, University of Oxford. Plasma samples were filtered through molecular weight cut‐off filters (10 kDa) to remove proteins 25 . The infranatant was recovered and evaporated to dryness under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Terminal fed blood samples were assessed for low molecular weight metabolites with Liquid Chromatography-Mass Spectrometry (LC-MS) within the Department of Chemistry, University of Oxford. Plasma samples were ltered through molecular weight cut-off lters (10kD) to remove proteins [25]. The infranatant was recovered and evaporated to dryness under reduced pressure.…”
Section: Metabolomicsmentioning
confidence: 99%
“…LC-MS: Acyl-carnitines were separated and resolved using hydrophobic-interaction liquid chromatography-mass spectrometry (HILIC). Samples were separated as previously outlined [25,26]. Brie y, samples were eluted using a binary solvent, acetonitrile:water (50%:50%) containing ammonium acetate (10mM nal concentration [Solvent A]) and acetonitrile:water (95%:5%) containing ammonium acetate (10mM nal concentration [Solvent B]).…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation